The Context Shift: Contestation as Expression of Will to Overcome the Impossible - Harutyunyan, Edvard (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
Life is much more significant than moving from one insufficiency to another. Life is an unfinished event and the human is an eternal Faust. The world must be constantly contested so that the life is not deprived of prospect. Contesting is a bid for architectonics of the world. The human has a a metaphysical surplus of energy and the aesthetical creation of the world is his incurable "disease".
Keywords: contestation, transgression, revolt, architectonics, expression of will, engineering, Alter, paradise